PENGARUH EXPERIENTIAL MARKETING, PRICE DAN SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION PADA PELANGGAN UP BARBERSHOP MAGETAN - Wahid Febryan Zakaria; Titi Rapini; Tegoeh Hari Abrianto (Gapenas Publisher, 2022)
This study was conducted to determine the effect of experiential marketing, price, and service quality on customer satisfaction at Up Barbershop Magetan customers. Determination of the sample used is by taking 10% of the population of the number of customers in 2021 at Up Barbershop. Collecting data in this study by distributing questionnaires to all respondents. The method of analysis in this study using multiple linear regression analysis. The results of this study indicate that: (1) There is a positive influence of experiential marketing on customer satisfaction, (2) There is a positive influence of price on customer satisfaction, (3) There is a positive influence of service quality on customer satisfaction, (4) There is a simultaneous influence of experiential marketing , price and service quality to customer satisfaction